Thyroid Dyshormonogenesis Presenting with Clinical Hypothyroidism Despite Biochemical Euthyroidism: A Case Report (Bangladesh Journal of Nuclear Medicine, 2026)
Thyroid dyshormonogenesis is an uncommon cause of congenital hypothyroidism resulting from inherited defects in thyroid hormone synthesis. Although most patients present with biochemical hypothyroidism, atypical presentations may occur. This report describes a case of thyroid dyshormonogenesis presenting clinical features of hypothyroidism despite normal thyroid function tests, emphasizing the need for further investigations. A 15-year-old boy presented with neck swelling and clinical features suggestive of hypothyroidism, but biochemical euthyroidism. Ultrasonography showed an enlarged heterogeneous thyroid gland with cystic nodules in both lobes. A 99mTc-pertechnetate thyroid scan demonstrated nonhomogeneous tracer concentration with diffuse thyroid enlargement. Radioiodine uptake testing followed by a perchlorate discharge test confirmed a defect in iodide organification consistent with thyroid dyshormonogenesis. The patient was subsequently referred to levothyroxine therapy and follow up. This case highlights an unusual clinicobiochemical discordance in thyroid dyshormonogenesis, where clinical manifestations of hypothyroidism may occur despite biochemical euthyroidism.Bangladesh J. Nuclear Med. 28(2): 374-378, 2025